The role of rat posterior parietal cortex in coordinating spatial representations during place avoidance in dissociated reference frames on a continuously rotating arena (Carousel) - Svoboda, Jan; Telensky, Petr; Blahna, Karel; Vodicka, Martin; Stuchlik, Ales (Behavioural brain research, 2015)
On the Carousel maze, rats are trained to avoid a sector of a circular rotating arena, punishable by a mild electric foot-shock. In the room frame (RF) variant, the punishable sector remains stable relative to the room, while in the arena frame (AF) version, the sector rotates with the arena. The rats therefore need to disregard local olfactory, tactile and self-motion cues in RF condition and distal extra-maze landmarks in the AF task. In both primates and rodents, the coordination of various spatial reference frames is thought to depend on the posterior parietal cortex (PPC). We have previously shown that PPC-lesioned rats can solve both variants of the Carousel avoidance task. Here we aimed to determine the effects of bilateral thermocoagulation lesion of the PPC in Long-Evans rats on the ability to transition between multiple spatial strategies. The rats were first trained in five sessions in one condition and then another five sessions in the other. The following training schemes were used: RF to AF, RF to RF reversal (sector on the opposite side), and AF to RF. We found a PPC lesion-associated impairment in the transition from the AF to RF task, but not vice versa. Furthermore, PPC lesion impaired performance in RF reversal. In accordance to the literature, we also found an impairment in navigation guided by intra-maze visuospatial cues, but not by extra-maze cues in the water maze. Therefore, the PPC lesion-induced impairment is neither specific to distant cues nor to allocentric processing. Our results thus indicate a role of the PPC in the flexibility in spatial behaviors guided by visual orientation cues.
Keywords: Parietal Lobe; chování zvířat; temenní lalok; Spatial Navigation; Maze Learning; elektrokoagulace; bludiště - učení; Rat; Orientation; krysa rodu Rattus; Reference frame; elektrický šok; zvířata; Avoidance Learning; Electroshock; Rats, Long-Evans; učení vyhýbat se; Male; Navigation; orientace; Electrocoagulation; potkani Long-Evans; Cues; Rats; podněty; prostorová navigace; Animals; Lesion; mužské pohlaví; Behavior, Animal; Posterior parietal cortex